Combining Microbial Culturing With Mathematical Modeling in an Introductory Course-Based Undergraduate Research Experience - Furrow, Robert E.; Kim, Hyunsoo G.; Abdelrazek, Samah M. R.; Dahlhausen, Katherine; Yao, Andrew I.; Eisen, Jonathan A.; Goldman, Mark S.; Albeck, John G.; Facciotti, Marc T. (Frontiers in Microbiology, 2020)
Quantitative techniques are a critical part of contemporary biology research, but students interested in biology enter college with widely varying quantitative skills and attitudes towards mathematics. Course-based undergraduate research experiences (CUREs) may be an early way to build student competency and positive attitudes. Here we describe the design, implementation, and assessment of an introductory quantitative CURE focused on halophilic microbes. In this CURE, students culture and isolate halophilic microbes from environmental and food samples, perform growth assays, then use mathematical modeling to quantify the growth rate of strains in different salinities. To assess how the course may impact students’ future academic plans and attitudes towards the use of math in biology, we used pre- and post-quarter surveys. Students who completed the course showed more positive attitudes towards science learning and an increased interest in pursuing additional quantitative biology experiences. We argue that the classroom application of microbiology methods, combined with mathematical modeling using student-generated data, provides a degree of student ownership, collaboration, iteration, and discovery that makes quantitative learning both relevant and exciting to students.